Open heart surgery patients’ education. a source of anxiety? - Kadda, Olga (Health & Research Journal, 2015)
In recent years the interest of health care professionals has focused on the process of patient pre and post operative education and in what way the psychological status is affected. They particularly emphasized the need to design effective and individualized trainings programs which concern preoperative and postoperative information, cardiac rehabilitation after open heart surgery so as to enhance patient’s comfort and anxiety reduction. The main idea of the programme is to change patient’s behaviour regarding modifiable risk factors and improve their quality of life. Moreover, the aim of the individual educational programme is to understand the surgical procedure, complications may occur, maintaining treatment compliance at a high level, the improvement of psychological status and quality of life not only for the patient but for its family too. Cardiac surgery is a very difficult process that causes a lot of stress and one of the most important nurse’s roles is to provide information and patient support throughout their recovery period.